Ready to Dare? A Case Study on the Entrepreneurial Intentions of Business and Engineering Students in Turkey - AŞKUN, OLCAY BİGE; ÇAKIR, ÖZGÜR (ELSEVIER SCIENCE BV, 2016)
Today entrepreneurship is accepted as the critical component of sustainable economic growth and employment creation. Entrepreneurship is not a simple plan-and-do act, and is a behavior that is resulted from the attitude that reflects an individual's motivation and capacity to identify an opportunity and to pursue it in order to produce new value or economic success. However the previous and determinant element towards performing entrepreneurial behavior is entrepreneurial intentions. Therefore, understanding the level of entrepreneurial intentions provides insights to policy makers and researchers for forecasting future entrepreneurship activities and the entrepreneurial potentials that can be utilized for achieving economic objectives. In other words, entrepreneurial intent that is defined as the intention of an individual to start their own business is the primary predictor of future entrepreneurs. In theoretical background, personal history, social context, attitudes toward entrepreneurship, planned behavior and personality traits are pointed out as factors that have impact on the propensity to engage in entrepreneurship, and these factors are categorized as internal (personality) and external (contextual or environment). For Turkey, some previous research focused on the entrepreneurial intentions of students. However, there is still room for research on the impacts of personality, university environment/education on entrepreneurial intent. Also the differences between the entrepreneurial intentions of students from different disciplines were rarely explored. In this context, study aims to define the level of entrepreneurial intentions as well as the impact of discipline (engineering vs. management) and gender in business administration and management engineering departments in two major public universities in Turkey. By this aim, we conducted a survey among total 446 students from these universities in the first and final term (1st and 4th grades). Survey Questionnaires are designed in the light of the theoretical background and Theory of Planned Behavior is revisited. Findings reveal that the entrepreneurial intentions of students are considerable for most of the constructs, while the educational programme, university and gender cause significant differences in the intent. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Entrepreneurship; Entrepreneurial intentions; Higher Education Institutions; SELF-EFFICACY; GENDER; MODEL